Uji Aktivitas Antibakteri Dari Ekstrak Etanol Bonggol Pisang Kepok (Musa paradisiaca L.) Terhadap Bakteri Staphylococus Aureus Dan Escherichia Coli Dengan Metode Difusi Agar - Angrestian, Angga; Renggana, Hesti; nugraha, Yogi rahman (Jurnal Medika Farmaka, 2024)
Medicinal plants that have more uses and value in traditional medicine against diseases. One of them is the kepok banana plant (Musa paradisiaca L.) as an herbal treatment the kepok banana plant is an annual shrub, this plant has a root system and rhizome Fruit only once (single fruit) then dies. Banana plants contain compounds such as flavonoids, saponins, tannins, and steroids. The method used in the research to be carried out is the experimental method. This study aims to determine the ethanol extract of kepok banana weevil (Musa paradisiaca L.) to test its antibacterial activity against Staphylococcus aureus and Escherichia coli using the agar diffusion method. In this study, the ethanol extract of kepok banana weevil (Musa paradisiaca L.) with concentrations of 2, 4, and 6 against Staphylococus aureus and Escherichia coli bacteria. In Staphylococus aureus bacteria with a concentration of 2 the average diameter of the inhibitor produced was 3.03 mm, the concentration of 4 of the diameter of the inhibitor produced was 6.4 mm, the concentration of 6 of the diameter of the inhibitor produced was 8.3 mm. In Escherichia coli bacteria with a concentration of 2 the average diameter of 6.7 mm was produced, the concentration of 4 was 7.7 mm in diameter, and the concentration of 6 was 8.2 mm in diameter. The three concentrations have antibacterial effect that is Resistant 14 mm. Ethanol extract of kepok banana weevil (Musa paradisiaca L.) can inhibit the growth of staphylococcus aureus and Escherichia coli bacteria. At concentrations of 2, 4, and 6 the ethanolic extract of the kepok banana weevil (Musa paradisiaca L.) with an average inhibitory diameter of 3.03 mm, 6.4 mm and 8.3 mm, these three concentrations had an antibacterial effect of 14 mm.